Dexmedetomidine sedation for a dental extraction in a patient with known difficult airway. Issue 2 (12th August 2022) - Guinness, F.; Coleman, M.; Gillbride, M.
Summary: Fibrodysplasia ossificans progressiva is an autosomal dominant condition that causes cervical spine fusion and ankylosis of the temporomandibular joint, resulting in anaesthetic challenges. Awake tracheal intubation with flexible bronchoscopy is recommended for general anaesthetics required by patients with this disease. This case report describes the novel approach of using dexmedetomidine sedation in combination with local anaesthesia to allow dental extraction of the fifth and seventh upper left teeth in a patient with fibrodyplasia ossificans progressive, who had a known difficult airway and profound thrombocytopenia. This procedure was not previously tolerated by the patient under local anaesthesia alone. The use of dexmedetomidine was successful in facilitating completion of the procedure with a high degree of patient satisfaction. We discuss the advantages of dexmedetomidine over other sedative agents due to its minimal effects on respiratory drive and airway muscle tone. We highlight the use of dexmedetomidine for complex cases such as this, where tracheal intubation is potentially challenging, but the procedure itself could be managed under sedation and local anaesthesia.